Variable area flowmeter handbook (Fischer & Porter Company, 1969)
The Allen p. Colburn, memorial flow laboratory provides basic standards for hydraulic calibration of Fischer & Porte flow meters. modern, precise calibrating facilities, simulating actual hydraulic operating conditions, assure the predictable calibration of F&P tri-Flat meters.